MANGROVE HEALTH INDEKS IN SEGARAJAYA VILLAGE TARUMAJAYA DISTRICT BEKASI REGENCY, WEST JAVA - Rizkiah, Riza; Wardono, Suko; Rosalina, Dwi; Handayani, Endy; Yusuf, Muhammad; Ismail, R. Moh.; Sulistiyo, Budi; Amdani, Amdani; Yohana Romauli, Angelina (Jurnal Segara, 2025)
Mangrove forests are types of vegetation that grow under the influence of the rising and falling sea water. They play a crucial role ecologically, physically, and economically. However, without proper management, this ecosystem is at risk of harm. In Segarajaya Village, Tarumajaya District, Bekasi Regency, West Java, mangrove forests are threatened by human activities, such as clearing land for fish farming without preserving mangrove vegetation, along with pollution from plastic and household waste. This study aimed to assess the health of mangroves based on two aspects: (1) MHI parameters, which include canopy cover, individual density, and stem diameter; and (2) environmental parameters, which consist of salinity, water and air temperature, soil pH, and substrate type. The method employed is the Mangrove Health Index (MHI), which involves calculating the parameters of canopy cover, stake density, and average stem diameter at breast height, along with environmental parameters (salinity, water and air temperature, soil pH, and substrate) conducted from February 25 to April 20, 2025. The observation site was divided into three stations. Station 1 had the species Rhizophora apiculata, Avicennia marina, and Sonneratia caseolaris. Station 2 was populated with Bruguiera gymnorhiza and Sonneratia caseolaris, while Station 3 only contained Avicennia marina. The MHI value calculations indicated that the mangrove forest's condition falls into the moderate category, with an average MHI value of 61.78%. Station 1 recorded 62.69%, Station 2 61.63%, and Station 3 61.02%. The average values of environmental parameters were a salinity of 30.44‰, water temperature of 27.94°C, air temperature of 30.89°C, soil pH of 7.33, and substrates consisting of sandy clay and mud. This study aims to inform readers about the health conditions of mangroves and serve as a foundation for managing and protecting mangrove forests.